Open Repair of Large Hepatic Artery Pseudoaneurysm Without Collateral Circulation: A Case Report - Wen, Xin; Chen, Xiyang; Zhao, Jichun; Luo, Xin; Guo, Qiang; Du, Xiaojiong; Yuan, Ding; Huang, Bin (Frontiers in Surgery, 2022)
Pseudoaneurysm of the hepatic innominate artery is a rare arterial disease. This case report describes a patient with hepatic artery pseudoaneurysm who suffered from recurrent epigastric pain for 4 months. Computed tomography angiography revealed that aneurysmal enlargement of hepatic artery from the common size of 55 mm×46 mm. Angiography showed that common hepatic artery aroused from pancreatoduodenal artery, and proper hepatic artery pseudoaneurysm derived from common hepatic artery was observed without collateral vessels. After comprehensive consideration, the patient was subjected to open surgery repair. The patient recovered well without any related complications. The patient’s 1-year follow-up did not reveal any late complications. The treatment choice, puzzles, and reflections of this case were discussed in this paper.